The Effect of Macroeconomic Conditions and the Global Economy on ISSI Stock Prices - Ahmad, Syafiq Malik (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research examines the impact of macroeconomic and global economic variables on ISSI stock performance using quantitative methods based on secondary data. By applying time series regression analysis with OLS (Ordinary Least Square), this study explores the relationship between macroeconomic variables, such as corporate production index, inflation, world oil price, world gold price, and Dow Jones Islamic Market, with changes in ISSI stock prices during the period January 2018 to July 2023. The results showed that the company's production index and the world oil price had a significant effect on the ISSI stock price. Meanwhile, inflation, world gold prices, and DJIM have no significant effect on ISSI stock prices. But overall the independent variables have a considerable influence on the movement of ISSI stock prices. The results of this study are expected to provide in-depth insight into the dynamics of ISSI stock prices and the relative contribution of macroeconomic and global factors in ISSI stock price movements.